Harmonisation of Dayak Customary Sanctions with Islamic Law: The Case Study of Dimly Lit Cafe in West Kalimantan - Asman, Asman (UIN Sunan Kalijaga Yogyakarta, 2025)
There are contradictions between the customary norms of the Dayak community and the phenomenon of dimly lit cafes in Sajingan Besar, West Kalimantan, which are often associated with deviant activities such as the sale of alcohol and hidden prostitution. On the one hand, the Dayak community imposes customary sanctions as a form of enforcement of local social and cultural norms; on the other hand, there has been no in-depth study to assess the extent to which these sanctions are consistent with the principles of Islamic law. The purpose of this article is to analyze the view of Islamic law on Dayak customary sanctions on the existence of dimly lit cafes and to explore the potential synergy between the two in maintaining morality and public order.This type of research is qualitative research with a normative sociological approach. Data sources consisted of primary data in the form of interviews with traditional leaders and local scholars, and secondary data in the form of Islamic literature, customary law, and social regulations. Data collection techniques were conducted through literature review and in-depth interviews, while data analysis techniques used descriptive-qualitative methods with content analysis and interpretive approaches. The results show that there are similarities between Dayak customary sanctions and Islamic legal principles, especially in terms of the purpose of maintaining social order and upholding moral norms. The novelty of this study lies in the comparative analysis between customary sanctioning mechanisms and the concept of hisbah in Islam, which have rarely been studied simultaneously in the local context of the Indonesia-Malaysia border. This research contributes to strengthening cross-cultural and religious understanding in upholding social norms, as well as providing positive implications for the formulation of local policies based on local wisdom values and Islamic principles in creating a harmonious society. Kontradiksi muncul antara norma adat masyarakat Dayak dan fenomena keberadaan café remang-remang di Sajingan Besar, Kalimantan Barat, yang sering dikaitkan dengan aktivitas menyimpang seperti peredaran minuman keras dan prostitusi terselubung. Di satu sisi, masyarakat Dayak memberlakukan sanksi adat sebagai bentuk penegakan norma sosial dan budaya lokal; di sisi lain, belum ada kajian mendalam yang menilai sejauh mana sanksi tersebut selaras dengan prinsip-prinsip hukum Islam. Tujuan dari penelitian ini adalah untuk menganalisis pandangan hukum Islam terhadap sanksi adat Dayak atas keberadaan café remang-remang serta menggali potensi sinergi antara keduanya dalam menjaga moralitas dan ketertiban masyarakat. Jenis penelitian ini adalah penelitian kualitatif dengan pendekatan normatif-sosiologis. Sumber data terdiri dari data primer berupa wawancara dengan tokoh adat dan ulama setempat, serta data sekunder berupa literatur keislaman, hukum adat, dan regulasi sosial. Teknik pengumpulan data dilakukan melalui observasi dan wawancara, sementara teknik analisis data menggunakan metode deskriptif-kualitatif dengan pendekatan analisis isi dan interpretatif. Hasil penelitian menunjukkan bahwa terdapat titik temu antara sanksi adat Dayak dan prinsip hukum Islam, terutama dalam hal tujuan menjaga ketertiban sosial dan menegakkan norma moral. Kebaruan dari studi ini terletak pada analisis komparatif antara mekanisme sanksi adat dan konsep hisbah dalam Islam, yang selama ini jarang dieksplorasi secara bersamaan dalam konteks lokal perbatasan Indonesia-Malaysia. Penelitian ini berkontribusi dalam memperkuat pemahaman lintas budaya dan agama dalam penegakan norma sosial, serta memberikan implikasi positif bagi perumusan kebijakan lokal yang berbasis pada nilai kearifan lokal dan prinsip-prinsip Islam dalam menciptakan masyarakat yang harmonis.